Case report: Sevelamer-associated colitis—a cause of pseudotumor formation with colon perforation and life-threatening bleeding - Fistrek Prlic, Margareta; Jelakovic, Mislav; Brinar, Marko; Grgic, Dora; Romic, Ivan; Marusic, Zlatko; Ivandic, Ema; Jelakovic, Bojan; Vukovic Brinar, Ivana; Krznaric, Zeljko (Frontiers in Medicine, 2023)
Chronic kidney disease (CKD) is a very common chronic non-communicable disease. Phosphate and calcium metabolism disorders are one of the most common features of CKD. Sevelamer carbonate is the most widely used non-calcium phosphate binder. Gastrointestinal (GI) injury associated with sevelamer use is a documented adverse effect but is underrecognized as a cause of gastrointestinal symptoms in patients with CKD. We report a case of a 74-year-old woman taking low-dose sevelamer with serious gastrointestinal adverse effects causing colon rupture and severe gastrointestinal bleeding.